O desafio dos hospitais privados no acesso ao investimento estrangeiro: uma análise da relação entre governança corporativa e o desempenho econômico-financeiro - Schwach, Christiane Garrido (2016)
With the opening of the Brazilian market of hospitals for foreign direct investment, authorized from January 2015, some challenges of the private hospitals and the healthcare market is to understand what the investors seek in hospitals to make financial contributions. Some issues as macroeconomic outlook of the market; growth potential of the health sector; knowledge of the risks; existence of attractive hospitals available and Corporate Governance (CG), are essential for the analysis of investors. The need to professionalize the management of hospitals and train more qualified professionals is because, of mergers and acquisitions in health operations, be preceded by a thorough study of economic and financial viability and the assessment of the hospital that will receive the contribution. In this way, openness to foreign capital, brings new concepts to the health sector, particularly as the need for adjustments in current management models, mainly as good CG practices. In this sense, the objective of this study is to analyze the CG practices grip level in hospitals of the National Association of the Private Hospitals (ANAHP), and its indicators of economic and financial performance, which make them attractive to foreign investment. In addition, it elaborated the following research question: What is the relationship between the principles of corporate governance and financial indicators of the hospitals associated with ANAHP within the multidimensional perspective. The methodology is a study of exploratory nature, using a nearly-experimental research strategy, classified as ex post facto. Given a quantitative assessment the research has a multivariate approach, using descriptive analysis, multidimensional scaling (MDS) and application of cluster model. It was found that the group with the highest percentage of member hospitals CG (75%) showed better indicators. This result showed a positive relationship between the economic and financial performance indicators and CG practices and illustrated that the greater transparency of information, the better the economic and financial analysis of hospitals who wish to seek foreign investment.